PENGARUH PERSONAL SELLING DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL SUZUKI ERTIGA PADA PT. UNITED INDOBALI CABANG TEUKU UMAR DENPASAR - Ida Bagus Trisna Wijayanthi; Wiryawan Suputra Gumi; I Gusti Ayu Swastiari (Forum Manajemen STIMI Handayani Denpasar, 2016)
Consumers in the decision to buy a product that offered much influenced bytheir perceptions of price, product, promotion, place (marketing mix) .Relationshipbetween prices and purchasing decisions that affect the prices consumers in makingpurchasing decisions, the higher the price the lower the purchasing decision ,otherwise if the low price turns higher purchasing decisions. Therefore employersmust be keen in setting the price of products to the market that the product issuccessful in the market. In addition to Personal selling price serves as a means ofpromotion and communication media to inform the existence of a product producedby the company to konsumen. The company able to assess and evaluate the extent towhich consumers recognize and know the products through message communicationsubmitted by the personal selling activities. Moreover, personal selling is a directcommunication between the companies represented salespeople (marketer and agent)which is expected to quickly detect response to customers and create sales. Base onthe research has been conducted to evaluate the influence of personal selling and theprice of the car purchasing decisions Suzuki Ertiga in PT. United Indobali BranchTeuku Umar showed personal selling prices and positive influence simultaneouslyand partially on purchasing decisions.